Arithmetische Funktionen in Mengen der Werte von Polynome mit ganzzahligen Koeffizienten - Uždavinys, R. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Уждавинис. Арифметические функции на множествах значений целочисленных полиномов R. Uždavinys. Aritmetinės funkcijos polinomų su sveikais koeficientais reikšmių aibėse